PENGUATAN KARAKTER TANGGUNG JAWAB MELALUI ORGANISASI PRAMUKA DI MADRASAH ALIYAH NEGERI 2 KOTA MADIUN - Sari, Aulia Nadya; Adi, Agus Satmoko (Universitas Negeri Surabaya (Unesa), 2024)
Strengthening character is an illustration of human qualities that must be developed by educational units, and is the basis for developing national character. Responsibility is a person's awareness of carrying out an activity and being willing to take risks as a result of the action. Scouting as an organizational activity in schools is very relevant to strengthening the character of responsibility. The aim of this research is to determine the implementation and obstacles to strengthening the responsible character of Scout organizational activities carried out at MAN 2 Madiun City. This research uses descriptive qualitative research, meaning it is to present a complete picture of an event or is intended to clarify a phenomenon that is occurring. Data collection techniques in this research used observation, interviews and documentation. Data analysis techniques use the Miles and Huberman model through data collection, data reduction, data presentation, and drawing conclusions. The theoretical basis for this research is the theory of character formation by Thomas Lickona. The results of the research show that strengthening the character of responsibility through the MAN 2 Madiun City Scout organization cannot be separated from the guidance of parents, school principals, Scout leaders and older brothers on the shelf council. Strengthening the character of responsibility through work programs or activities, namely routine Fridays, reception of visiting guests, inauguration of Bantara, inauguration of implementing, large camps, and hiking. During the process of strengthening the character of responsibility in students, there are obstacles that are difficult for students to manage, even hot weather. which makes it less supportive of outdoor Scout activities. So there is a need for strategies such as socialization, firmness when there are students who do not obey orders, and creating meeting or evaluation forums for discussion.